Determining the Effects of Aqueous Extract of Rhizomes of Zingiber officinale (Ginger) on Sexual Parameters in Female Wistar Rats - Peneme B. M. L.; Akassa H.; Ondélé R.; Backala Lanzah A.; Etou Ossibi A. W.; Abena A. A. (Medical Research and Its Applications Vol. 1, 2024)
The present study aims to evaluate the effects of the aqueous extract of Zingiber officinale (Ginger) rhizomes on reproductive parameters in female Wistar rats. The rhizome of Zingiber officinal (Ginger) is widely consumed as a juice and spice in the Congo and is also used in the treatment of various pathologies. Modern Western medicine has ignored most of these resources by developing chemical drugs and sophisticated treatment techniques while continuing to use certain plant remedies. Four batches of four female rats each received the aqueous rhizome extract of Zingiber officinal (Ginger) at doses of 300 and 600 mg/kg, 17\(β\)-estradiol at a dose of 1 mg/kg and distilled water, orally for 14 aqueous ginger extract non-significantly increased and decreased rat body weight at 300 and 600 mg/kg respectively. The 600 mg/Kg dose blocked the sexual cycle at the estrus stage and lowered plasma estradiol levels. Whereas the 300 mg/kg dose increases plasma estradiol levels with a more or less regular sexual cycle. Chemical screening of this extract revealed the presence of flavonoids, tannins, anthraquinones and steroids. It would be desirable to evaluate sub-acute and chronic toxicity studies of the aqueous extract of Ginger rhizomes and the effects of this extract on sexual parameters in male rats. Also, to develop an improved traditional medicine for the treatment of reproductive disorders.